1999
DOI: 10.1002/(sici)1099-1379(199901)20:1<133::aid-job911>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gender in organizational justice perception

Abstract: SummaryTwo studies were used to examine the moderating eect of gender on the justice± outcome relationships. Contrary to hypothesis, gender moderates the relationship between distributive justice and trust in supervisor in sample 1. It is possible that women are concentrating more on distributive issues rather than procedural justice issues in order to address past pay discrepancies. Further, gender did not moderate any other justice±outcome relationships. These results may indicate a recent trend toward work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 17 publications
8
76
0
2
Order By: Relevance
“…They were included because previous research has shown that these demographics might be associated with commitment, justice perceptions, and turnover intentions (e.g., Lee & Farh, 1999). Age and organization tenure were measured in years.…”
Section: Control Variablesmentioning
confidence: 99%
“…They were included because previous research has shown that these demographics might be associated with commitment, justice perceptions, and turnover intentions (e.g., Lee & Farh, 1999). Age and organization tenure were measured in years.…”
Section: Control Variablesmentioning
confidence: 99%
“…This study had a limited number of male participants, in comparison with female participants, and did not examine the possibility that gender differences could be involved in the effects of justice and framing. Some studies have reported gender differences in justice perception (e.g., Lee & Farh, 1999;Sweeney & McFarlin, 1997) and the framing effect (e.g., Huang & Wang, 2010). Further study is needed to examine the moderating effect of gender differences on the relationship between justice and framing effects.…”
Section: Discussionmentioning
confidence: 99%
“…As women tend to experience inequity in rewards more than men (Gerhart 1990;Heberfeld and Sherhau 1990), they are likely to be more concerned with injustice events (Lee and Farh 1999;Sweeny and MacFarlin 1997;Fields et al 2000). Accordingly, the more injustice they perceive in school, the less likely they are to be committed to it and the more likely they are to be late than male teachers.…”
Section: Organizational Commitment As Mediating Distributive Justice mentioning
confidence: 99%
“…Studies indicate that women earn less than men and are promoted less (Blau et al 2005;Gerhart 1990; Heberfeld and Sherhau 1990) and that women may be adversely affected by distributive justice issues more than men (Lee and Farh 1999). In keeping with exchange theory, there is therefore reason to suspect that women would be inclined to be late more than men in order to achieve justice, balancing their timely or late arrival with the rewards they believe they get or do not get from the organization.…”
Section: Introductionmentioning
confidence: 99%